Welding engineering student learning outcomes in SMAW subjects: The effect on interest in entrepreneurship - Purnawirawan, Rendi; Yoto, Yoto; Suhartadi, Syarif (Journal of Research in Instructional, 2023)
This study aims to determine the influence of the learning outcomes of Shielded Metal Arc Welding (SMAW) subjects on the entrepreneurial interest of students at SMK Negeri 1 Udanawu, Blitar Regency. This research method is quantitative Research. Data collection techniques in this study used questionnaire and documentation methods. Data analysis uses validation tests, reliability tests, and simple linear regression analysis. The results showed that the F-count of 93.931 was greater than the F-table by 4.00. The significance of F by 0.002 was smaller than the α of 0.05, so the study results could be concluded that the variable learning outcomes of the SMAW subject had a significant effect on the variable of entrepreneurial interest of students. The results showed an R-value of 0.834, meaning that the relationship between the learning outcomes of Manual Arc Welding (SMAW) subjects and the entrepreneurial interest of students at SMK Negeri 1 Udanawu, Blitar Regency was very strong. This level of relationship can be categorized as a very strong relationship. This can be seen from the correlation value of 0.834 and the coefficient value between 0.800-1.000, which states the level of a very strong relationship. The value of the coefficient of determination is 71.5%, while the remaining 28.5% is influenced by other independent variables that were not studied in this study.